Geodetic Mass Balance of the Northern Patagonian Icefield from 2000 to 2012 Using Two Independent Methods - Dussaillant, Inés; Berthier, Etienne; Brun, Fanny (Frontiers in Earth Science, 2018)
We compare two independent estimates of the rate of elevation change and geodetic mass balance of the Northern Patagonian Icefield (NPI) between 2000 (3,856 km2) and 2012 (3,740 km2) from space-borne data. The first is obtained by differencing the Shuttle Radar Topography Mission (SRTM) digital elevation model (DEM) from February 2000 and a Satellite pour l'Observation de la Terre 5 (SPOT5) DEM from March 2012. The second is deduced by fitting pixel-based linear elevation trends over 118 DEMs calculated from Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) stereo images acquired between 2000 and 2012. Both methods lead to similar and strongly negative icefield-wide mass balance rates of −1.02 ± 0.21 and −1.06 ± 0.14 m w.e. yr−1 respectively, which is in agreement with earlier studies. Contrasting glacier responses are observed, with individual glacier mass balance rates ranging from −0.15 to −2.30 m w.e. yr−1 (standard deviation = 0.49 m w.e. yr−1; N = 38). For individual glaciers, the two methods agree within error bars, except for small glaciers poorly sampled in the SPOT5 DEM due to clouds. Importantly, our study confirms the lack of penetration of the C-band SRTM radar signal into the NPI snow and firn except for a region above 2,900 m a.s.l. covering <1% of the total area. Ignoring penetration would bias the mass balance by only 0.005 m w.e. yr−1. A strong advantage of the ASTER method is that it relies only on freely available data and can thus be extended to other glacierized areas.